Arunco-Fagetum Ž. Košir 1962 var. geogr. Acer obtusatum var. geogr. nov. v dolini zgornje Kolpe - Accetto, Marko (Gozdarski vestnik, 2007)
In his article, the author describes a new geographic variant of the association Arunco-Fagetum var. geogr. Acer obtusatum growing on the steep cold slopes of the mountain and partly high mountain belt of the upper Kolpa River Valley. The differential species of the geographical variant is the species Acer obtusatum and the edaphic differential species are the species Omphalodes verna, Euphorbia carniolica, Pulmonaria stiriaca and Erythronium dens-canis. He divides the geographical variant into three sub-associations: -fraxinetosum excelsioris, - typicum and - homogynetosum sylvestris. The new geographic variant is based on the detailed comparison of the floristic, phytosociological and geo-elemental structure and on the spectrum of biological plant forms similar to the beech forests in the pre-dinaric phytogeographical area of Slovenia.
Keywords: fitocenologija; phytosociology; bukovi gozdovi; rastlinske združbe; Kolpska dolina; Kočevsko; Slovenia; Slovenija